Analisis Komunikasi Interpersonal Antar Mahasiswa President University - Muhammad Arbi Badawi Arbi Badawi; Dedi Rianto Rahadi (Communicology: Jurnal Ilmu Komunikasi, 2021)
ABSTRACT Interpersonal communication is one type of communication that is not formally regulated and is a form of direct or face-to-face communication. This study aims to determine President University students carry out interpersonal communication, the main thing is to do so that interpersonal communication runs well and effectively between students. The research method in this study is descriptive qualitative. Informants will answer several questions related to the topic of discussion through an online form. The results showed that interpersonal communication is important and is an activity carried out in daily life by President University students. Interpersonal communication is important according to President University students, and is an activity carried out in daily life to support student activities in socializing and getting along with the environment. Keywords: Communication; Communication between Students; Interpersonal Communication